Effects of Tai Chi on health status in adults with chronic heart failure: A systematic review and meta-analysis - Hui, Jiaqi; Wang, Ya; Zhao, Junnan; Cong, Weihong; Xu, Fengqin (Frontiers in Cardiovascular Medicine, 2022)
Background Chronic heart failure (CHF) is among the top causes of cardiovascular morbidity, and most patients with CHF have poor health status. Tai Chi, a mind-body exercise that originated in China, is beneficial for health status. This study was conducted to evaluate the effects of Tai Chi on health status in adults with CHF. Methods The Cochrane Library, PubMed, Embase, Web of Science, China National Knowledge Infrastructure, Wanfang Database, Chinese Biomedical Database, and Chinese Scientific Journal Database were searched from the inception to 22 October 2021. This meta-analysis was performed using the fixed- or random-effects model. Continuous outcomes were carried out using mean difference (MD) or standardized mean difference (SMD) with 95% confidence interval (CI). Dichotomous outcomes were determined using risk ratio (RR) with 95%CI. The Grading of Recommendations, Assessment, Development and Evaluations (GRADE)pro Guideline Development Tool (GDT) online software was used to present outcome-specific information regarding overall certainty of evidence from studies. Results In total, 15 studies including 1,236 participants were finally included. Compared with usual care alone, Tai Chi combined with usual care achieved efficacy in improving Minnesota Living with Heart Failure Questionnaire (MD = −8.51; 95% CI: −10.32 to −6.70; p < 0.00001), 6-min walk test (MD = 43.47; 95% CI: 33.38 to 54.10; p < 0.00001), left ventricular ejection fraction (MD = 6.07; 95% CI: 3.44 to 8.70; p < 0.00001), B-type natriuretic peptide/N-terminal fragment of pro-BNP (SMD = −1.12; 95% CI: −1.70 to −0.54; p = 0.0002), Hamilton Depression Rating Scale (MD = −2.89; 95% CI: −4.87 to −0.91; p = 0.004), Pittsburgh Sleep Quality Index (MD = −2.25; 95% CI: −3.88 to −0.61; p = 0.007), timed up and go test (MD = −1.34; 95% CI: −2.50 to −0.19; p = 0.02), and reduced the risk of heart failure hospitalization (RR = 0.47; 95% CI: 0.25 to 0.88; p = 0.02). However, there was no difference in the outcome of peak oxygen uptake (MD = 1.38; 95% CI: −1.51 to 4.28; p = 0.35). All-cause mortality or cardiovascular death could not be evaluated due to insufficient data. The certainty of evidence ranged from very low to moderate due to the risk of bias, inconsistency, imprecision, and publication bias. Conclusion Tai Chi might be safe and showed beneficial effects on health status in patients with CHF. However, more high-quality and long-term studies are still needed to further evaluate the effects of Tai Chi.